Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
no solution
Step-by-step explanation:
Given equation:
3(2x + 4) - 8x = -2(x + 1) + 3
Expand the brackets:
⇒ 3(2x) + 3(4) - 8x = -2(x) - 2(1) + 3
⇒ 6x + 12 - 8x = -2x - 2 + 3
Collect like terms:
⇒ 6x - 8x + 12 = -2x - 2 + 3
Combine like terms:
⇒ -2x + 12 = -2x + 1
Subtract 12 from both sides:
⇒ -2x + 12 - 12 = -2x + 1 - 12
⇒ -2x = -2x - 11
Add 2x to both sides:
⇒ -2x + 2x = -2x +2x - 11
⇒ 0 = -11
The sides are not equal, therefore there is no solution
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.